1987
DOI: 10.1007/bf01655820
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and indications for perfusion in liver tumors: Current data

Abstract: Current DataSince Novermber, 1981, 50 patients (predominantly those with metastases of coiorectal carcinomas) have been treated in our clinic by an isolated regional chemotherapy on an average of 9 months after the primary operation. The mortality rate was 8%.The eytostatic drugs applied alone or in combination were 5fluorouracil (5-FU) (300-1,250 mg) and mitomycin C (5-50 mg) in 46 patients, and 5-FU, mitomycin C, and cisplatin (50 mg) in 4 patients. The course of the disease was observed in 41 patients. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Aigner et al 21 reported safe doses of 5-FU between 700 and 1,100 mg delivered with hyperthermia as an hour-long perfusion in 32 patients. Schwemmle et al 22 reported 5-FU (300–1,250 mg) delivered in combination with mitomycin C as an isolated hepatic perfusion in 50 patients. This discrepancy between our MTD and the doses previously given likely represent temporal differences in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Aigner et al 21 reported safe doses of 5-FU between 700 and 1,100 mg delivered with hyperthermia as an hour-long perfusion in 32 patients. Schwemmle et al 22 reported 5-FU (300–1,250 mg) delivered in combination with mitomycin C as an isolated hepatic perfusion in 50 patients. This discrepancy between our MTD and the doses previously given likely represent temporal differences in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this trial of the ALM, the trial arm with 5-HAI-FUDR had similar response rates as HAI with 5-FU plus FA, but a lower survival time at a remarkable hepatic toxicity that was not present in HAI or systemic therapy with 5-FU plus FA (Table 2) [55]. Various trials involving stop-flow infusion, microsphere infusion, or isolated liver perfusion have been conducted, but none of those trials improved the median survival time versus "conventional" HAI or systemic treatment [5, 25,65,68,69], although the number of long-term survivors after isolated liver perfusion (+HAI) was remarkable [2].…”
Section: Literature Resultsmentioning
confidence: 95%
“…The response rate was 48% and survival time 19 months. The High-effort techniques applying either HAI with microspheres [68,69], stop-flow techniques [25] or isolated liver perfusion [2,65] may increase response rates compared with conventional HAI, but a significant prolongation of median survival times has not been proven.…”
Section: Use Of 5-fudr For Hai Causes Sclerosing Cholangitismentioning
confidence: 99%
“…In their series, median survival was 8 months, and no response data were reported. Schwemmle et al [36] observed a 22% complete response and a 68% partial response rate after IHP with 5-FU/MMC/cisplatin. In contrast, Hafstrome et al [37] reported in 1994 their results of IHP with melphalan and cisplatin in 29 patients and observed a response rate of only 20% and a mortality rate of as much as 14%.…”
Section: Results In Chm Patientsmentioning
confidence: 99%